Językowe zabawy w wierszach Małgorzaty Strzałkowskiej - Kaptur, Ewa (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
The article presents the linguistic games in selected poems by Małgorzata Strzałkowska. The subject of the research were 300 works from ten volumes that have been published over the last twenty-five years. The text examines these verbal games, which are mainly based on the sound layer of the utterance, i.e. sounds / sounds, onomatopoeia, rhymes, and rhythm. It was found that Strzałkowska’s poems can be ready-made lesson plans that can be used in Polish lessons, in phonetics, in voice emission as well as during speech diagnosis or therapy.